Kokspilleri i kolonihaver: en kulegravning - Erlandsen, Hikoline Hylleborg (Arbejderhistorie, 2026)
This article explores the little-known practice of digging for coke residues (“pillekoks”) in Copenhagen allotment gardens during both WWI and WWII. Due to the fuel shortages and rising prices many working-class families turned to collecting pillekoks, unburned coke discarded as ash, in former waste sites that was converted into parks and allotment gardens. Using ethnological surveys from the 1970s and contemporary newspapers, the study shows this was a widespread practice with significant yields. individual allotment owners could gather enough pillekoks with a value equivalent to several weeks’ wages, easing fuel scarcity and improving daily life during wartime. While important, this practice has been little studied. This article attempts to shed light on the economic and social role of pillekoks digging and suggests that more research is needed on wartime fuel use and the role of allotment gardens in wartime.